O antioxidante mitocondrial, mitoquinona, previne a disfunção cardíaca 7 dias após infarto do miocárdio em rato - Ximenes, Carolina Falcão (2023)
Myocardial Infarction (AMI) is considered the main cause of heart failure (HF). It is believed that oxidative stress (ROS) plays a crucial role in the myocardium adjacent to the infarcted area and in the progression of left ventricular remodeling. At 7 days post-AMI, the decrease in myocardial contractility is associated with changes in the pathway of calcium (Ca2+) and ROS. However, the impact of mitochondrial ROS as a source of controlled dysfunction during the early phase of AMI will remains unknown. We hypothesize that MitoQ mitochondrial antioxidant treatment for 7 days after AMI will improve contractile function dependent on the reduction in mitochondrial ROS production in the acute phase of AIM. Therefore, our objective was to analyze the effect of treatment, for 7 days, with the specific mitochondrial antioxidant, MitoQ, on contractile dysfunction in the acute phase after AMI in rats. Wistar rats aged 12 weeks were divided into Sham, Infarto, Sham MitoQ and Infarto MitoQ (CEUA 16/2021). At the end of treatment with MitoQ for 7 days in drinking water (100 µM), analyzes of myocardial contractility “in vivo” were performed in hemodynamic parameters and “in vitro” measured in isolated papillary left ventricle (LV) with muscle length in which the active voltage is maximum (Lmáx); in presence of different extracellular concentrations of MitoQ; Ca2+ and isoproterenol. Cardiomyocytes isolated from the LV were used to measure morphological and temporal parameters of contractile function and transient Ca2+. Superoxide anion (O2 •- ) production was quantified using Dihydroethidium (DHE) and mitochondrial O2 •- using MitoSox Red. Statistical analysis used ANOVA two-way and post-hoc de Tukey’s and test t student, for p<0,05. Treatment with MitoQ did not change the area of infarction, However, it prevented the decrease in body weight gain and prevented the hemodynamic changes observed in the infarction group in the following parameters: systolic blood pressure (SBP) Sham: 113 ± 3; Infarto: 93 ± 4; Sham MitoQ: 108 ± 4; Infarto MitoQ: 108 ± 3*, mmHg *p<0.05); diastolic blood pressure (DBP) (Sham: 84 ± 3; Infarto: 68 ± 3; Sham MitoQ: 81 ± 3; Infarto MitoQ: 108 ± 3*, mmHg*p<0.05); left ventricular systole pressure (LVSP) (Sham: 116 ± 4.5; Infarto: 79 ± 2.7; Sham MitoQ: 115.8 ± 6; Infarto MitoQ: 100 ± 4.4*, mmHg *p<0.05); left ventricular end-diastolic pressure (LVDP) (Sham: 5 ± 0.4; Infarto: 10 ± 1; Sham MitoQ: 3 ± 1; Infarto MitoQ: 5 ± 0.5*, mmHg *p<0.05); first derivate of maximum pressure (dP/dtmáx) (Sham: 3993 ± 199; Infarto: 2480 ± 58; Sham MitoQ: 3326 ± 265; Infarto MitoQ: 2738 ± 103*, mmHg/s *p<0.05) and first derivate of minimum (dP/dtmin) (Sham: -3273 ± 227; Infarto: -1486 ± 41; Sham MitoQ: -2703 ± 88; Infarto MitoQ: -2083 ± 88*, mmHg/s *p<0,05). Treatment with MitoQ (100 uM) for 7 days was able to prevent the reduction of the isometric force of contraction of the animals in the infarction group (Sham: 0.56 ± 0.06; Infarto: 0.29 ± 0.05; Sham MitoQ: 0.47 ± 0.07; Infarto MitoQ: 0.73 ± 0.08* g/mg, *p<0.05), the reduction of the maximum positive derivative of force (+dF/dtmáx) (Sham: 25 ± 2.18; Infarto: 14.43 ± 2.20; Sham MitoQ: 16.88 ± 2.16; Infarto MitoQ: 24.17 ± 1.75 g/g/s, *p<0.05) and reduced contractility to extracellular Ca2+ influx (1,25 mM – Sham: 444 ± 49.86; Infarto: 229.83 ± 68.28; Sham MitoQ: 357.38 ± 29.97; Infarto MitoQ: 640.17 ± 60.9* g/g, *p<0.05). Morphometric analyses observed that treatment with MitoQ prevented the increase in cell area (Sham: 3846 ± 105; Infarto: 4309 ± 107; Sham MitoQ: 4107 ± 134; Infarto MitoQ: 3782 ± 116* µm2 , *p<0.05) and increased cell length (Sham: 141 ± 2.8; Infarto: 153 ± 1.95; Sham MitoQ: 144 ± 2.25; Infarto MitoQ: 137 ± 2.25* µm, *p<0,05) of cardiomyocytes in the initial stage of AMI. The cardiomyocytes contractility was increased in the Infarto group, which were prevented by MitoQ treatment such as cardiomyocyte shortening (Sham: 610 ± 26; Infarto: 815 ± 30; Sham MitoQ: 653,5 ± 25; Infarto MitoQ: 553,6 ± 30* µm2 , *p<0.05). MitoQ treatment prevented the increase in [Ca2+]i transient amplitude (Sham: 2.58 ± 0.04; Infarto: 3.15 ± 0.07; Sham MitoQ: 2.65 ± 0.08; Infarto MitoQ: 2.30 ± 0.05* F/F0, *p<0.05). The in-situ production of O2 •- , demonstrated by fluorescence intensity, was higher in the Infarto group, but treatment with MitoQ for 7 days prevented this increase in ROS. Mitochondrial O2 •- formation in isolated cardiomyocytes was greater in the Infarto group compared to the Sham group (p<0.01), and MitoQ treatment restored redox homeostasis. Our results demonstrated that MitoQ treatment prevented contractile dysfunction, confirming the involvement of mitochondrial ROS participation in the development of HF after AMI. In this way, find the most effective and safe way to modulate mitochondrial function and dynamics in HF after AMI in its initial phase represents a potential therapeutic target and an important step for the future of research in the treatment of cardiovascular diseases.